The Fourth Plan Mid-Term Appraisal Volume I - Planning Commission (Planning Commission Government of India, 1971)
The Mid-Term Appraisal of India’s Fourth Plan (December 1971) provides a comprehensive evaluation of the country’s developmental progress, highlighting achievements, shortcomings, and policy recommendations. Despite a targeted annual growth rate of 5.6%, actual growth averaged 5% during the first two years, with agricultural performance slightly exceeding targets (5.2%) and industrial growth lagging significantly (4.1%). The appraisal emphasizes the need for enhanced resource mobilization, increased domestic savings, import substitution, and revitalization of public sector enterprises to ensure sustainable economic development. Financial assessments reveal significant shortfalls in projected revenues from public enterprises and states, leading to an overall resource gap of Rs. 4,594 crores, necessitating stricter fiscal control, deficit financing limits, and incentivizing private and public savings. Strategic recommendations also focus on rural development, employment generation, public health, education, and regional equity. The appraisal underscores the urgency of coordinated action across governance levels to achieve long-term self-reliant growth and socio-economic stability.
Government of India Planning Commission December 1971
Keywords: Fourth Plan; Economic Growth; Public Saving; Resource Mobilization; Industrial Performance; Agricultural Development; Deficit Financing; Domestic Investment; Public Enterprises; Regional Development; Self-Reliance; Fiscal Policy